2008
DOI: 10.1021/la801861q
|View full text |Cite
|
Sign up to set email alerts
|

Monolayers of 3-Mercaptopropyl-amino Acid to Reduce the Nonspecific Adsorption of Serum Proteins on the Surface of Biosensors

Abstract: Monolayers prepared with polar or ionic amino acids with short side chains have a reduced nonspecific adsorption of serum proteins compared to that of hydrophobic amino acids and organic monolayers immobilized on the gold surface of surface plasmon resonance (SPR) biosensors. Proteins contained in biological samples adsorb on most surfaces, which in the case of biosensors causes a nonspecific response that hinders the quantification of biomarkers in these biological samples. To circumvent this problem, self-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 49 publications
(92 reference statements)
3
107
0
Order By: Relevance
“…The results (Fig. 5) indicate that the electrochemical signal backgrounds observed on the Au electrode modified by oxinate functional group depends highly on the nature of the spacers, so that the backgrounds were minimized upon using azo spacer [14,86] formed by ATP and maximized upon using two amide spacers formed by glycine [87] (Supplementary Data, Fig. S9).…”
Section: Effect Of Linking Spacermentioning
confidence: 99%
“…The results (Fig. 5) indicate that the electrochemical signal backgrounds observed on the Au electrode modified by oxinate functional group depends highly on the nature of the spacers, so that the backgrounds were minimized upon using azo spacer [14,86] formed by ATP and maximized upon using two amide spacers formed by glycine [87] (Supplementary Data, Fig. S9).…”
Section: Effect Of Linking Spacermentioning
confidence: 99%
“…Our previous studies investigated the relationship of organic and peptide surface chemistries as a function of nonspecifically bound material: proteins from serum [5][6][7][8] and lipids from cell lysate [15]. It was found that nonspecifically bound proteins were more abundant on organic surfaces than peptide surfaces.…”
Section: Influence Of the Surface Chemistry On Biomolecule Transfer Tmentioning
confidence: 99%
“…However, plasmonic biosensors remain largely susceptible to nonspecific adsorption, limiting their applications in biofluids [1,2]. Recently, new surface chemistries based on zwitterionic polymers [3,4] or peptide chemistry [5][6][7] demonstrated the capacity of plasmonic biosensors for the detection of biomarkers in biofluids. While these surface chemistries effectively suppress a large fraction of the nonspecific adsorption of biofluids, their mechanism of action remains poorly described due to the difficulty of identifying nonspecifically adsorbed molecules with surface plasmon resonance (SPR) [8].…”
Section: Introductionmentioning
confidence: 99%
“…A peptide-like polymer was synthesized to limit cell adhesion to a surface for up to two weeks [20]. Amino acid monolayers are capable of low nonspecific adsorption and immobilize antibodies to detect sub-µM protein concentration [21]. Short peptides demonstrated low self-aggregation on gold nanoparticle, demonstrating low interactions between the peptides [22; 23].…”
Section: Introductionmentioning
confidence: 99%